Harmonized Scenario-Based Laboratory Coding System to Guide Real-Time Public Health Actions in Quebec Province, Canada. (March 2022) - Goupil-Sormany, I.; Longtin, J.; Rouleau, I.; Fafard, J.; Gilbert, N.; Cormiers, A. Des; Toth, E.
Abstract : Purpose: Effective public health (PH) response to emerging pathogens requires effective information systems integrating surveillance data from multiple sources. For laboratories, data entry of multiple variables both at pre-analytical steps and again in laboratory information systems (LIS) is time-consuming and difficult to implement in a resource-limited setting and negatively affects the timeliness of the surveillance system. We set up a simple harmonized laboratory query that summarized 22 public-health relevant scenarios and variables, reduced to a two-digit code. Methods & Materials: Information data specialists were mobilized to integrate data from the 108 different LIS using the harmonized query, which provided timely access to COVID-19 testing indications, volumes, and positivity rates stratified by age, health region, clinical settings, outbreak context or Health-Care worker status. The information system allowed to develop multiple indicators for a better understanding of the pandemic and the COVID-19 transmission in population subgroups. Results: Dashboards were available for public health and infection prevention and control officers in their location. Multiple stakeholders were able to interpret real-time data for more than 40 000 different qPCR tests every day. The data allowed to adjust prescription practice and promote optimal usage and plan contingencies within Quebec's qPCR lab capacities. It also served as the basis to monitor community transmission through test positivity rate in various settings. The coding system also allowed labs to easily implement sample triage, which reduced turnaround time to less than 24h for most samples. Starting May 2021, public health authorities add monitoring of the positive predictive value of rapid antigen test used at the community level to support evidence-based public health decisions about the best possible use of those assays. Conclusion: This simple scenario-based coding system allowed timely PH and management of both sampling and processing priorities which proved most useful during surge periods. Quebec Public Health Authorities were better able to target preventive actions and to plan outreach screening activities in subpopulations, neighbourhoods, and communities, while modulating clinical criteria to get access to testing and allowing laboratories to better triage samples.